THE WEAPONISATION OF EVERYTHING : A FIELD GUIDE TO THE NEW WAY OF WAR - Galeotti, Mark (Yale University Press, 2022)
"Hybrid War, Grey Zone Warfare, Unrestricted War: today, traditional conflict-fought with guns, bombs, and drones-has become too expensive to wage, too unpopular at home, and too difficult to manage. In an age when America threatens Europe with sanctions, and when China spends billions buying influence abroad, the world is heading for a new era of permanent low-level conflict, often unnoticed, undeclared, and unending. Transnational crime expert Mark Galeotti provides a comprehensive and ground-breaking survey of the new way of war. Ranging across the globe, Galeotti shows how today's conflicts are fought with everything from disinformation and espionage to crime and subversion, leading to instability within countries and a legitimacy crisis across the globe. But rather than suggest that we hope for a return to a bygone era of "stable" warfare, Galeotti details ways of surviving, adapting, and taking advantage of the opportunities presented by this new reality."